Memanfaatkan Aspek Pengetahuan, Sikap, dan Praktik sebagai Alternatif untuk Mencegah Dampak Buruk Stunting: Leveraging the Aspects of Knowledge, Attitude, and Practice as an Alternative to Prevent Detrimental Impacts of Stunting - Luthviatin, Novia; Rohmawati, Ninna; Wati, Dwi Martiana; Darmaningtyas, Jihan; Pasha, Yessinia Hanatha (Amerta Nutrition, 2024)
Background: The prevalence of stunting in Indonesia is recorded at 21.6% among children under five, while the WHO target for 2025 is less than 14%. Prevention efforts are crucial for mitigating its detrimental impacts. One of the early prevention efforts is health education about nutrition through strengthening knowledge, attitudes, and practices related to healthy food consumption. Objectives: This study aimed to measure the differences in the levels of knowledge, attitudes, and practices in school-age children following health education about nutrition. Methods: This study used a pre-experimental method involving 40 students aged 13 to 15 years. All students received nutritional health education through drama performances and lectures about healthy food and practiced bringing healthy packed meals at certain times. Data were analyzed using the Wilcoxon test and Friedman test. Results: Descriptive analysis showed an increase in the average values of knowledge, attitudes, and practices. The Wilcoxon test revealed a significant increase in knowledge (p-value=0.035) before and after the intervention. Meanwhile, the Friedman test revealed a significant increase in practices (p-value<0.001) before and after the intervention, with the practice of bringing and consuming healthy packed meals remaining consistent up to four weeks after the intervention. Conclusions: Interventions using drama performances, lectures, and the provision of healthy packed meals significantly increased knowledge and practices among junior high school students. These interventions can be used by schools and related agencies to promote the habit of bringing healthy food to prevent the negative impacts of stunting.